Pengembangan Perangkat Pembelajaran Matematika Model Project Based Learning Terintegrasi Stem Untuk Meningkatkan Kemampuan Berfikir Kreatif Peserta Didik Kelas VIII SMP - Ridha Fajria; Yerizon Yerizon; Edwin Musdi; Dony Permana (Universitas PGRI Madiun, 2022)
Learning tools become one of the important things in the learning process that has an impact on the ability of students, especially the ability to think creatively. Learning tools in the form of RPP and LKPD can create an effective and fun learning process, and can facilitate students' creative thinking skills. Although this creative thinking ability is one of the important abilities and must be mastered by students, there are still many students who find it difficult to solve problems that can encourage the development of students' creative thinking skills, so it is necessary to develop learning tools that can help improve students' abilities. creative thinking of students. Learning according to these characteristics is the STEM integrated Project Based Learning model of mathematics learning. This study aims to design valid, practical and effective learning tools in the form of STEM-PjBL-based RPP and LKPD for Class VIII Junior High School students. The development research was carried out using the Plomp development model. The Plomp development model consists of three stages, namely the preliminary research stage, the development or prototyping stage and the assessment stage. Data were collected through questionnaires, interviews and observation sheets. Analysis of the validity data showed that the resulting device was in the very valid category with a RPP validity score of 3.63 and LKPD 3.54. In the analysis of practicality data, it was found that the mathematics learning tools were practical with a practicality score of 82.1% for RPP and LKPD 82%. Learning tools are effective based on learning outcomes where the completeness is 63.02 %. Based on the results of the study, it was concluded that the STEM-PjBL-based learning tools developed were valid, practical and effective.